(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The paper presents life stories of the two greatest women physicists – Marie Sklodowska Curie, a Polish physicist and the only woman double Nobel Prize laureate, and Lise Meitner, an Austrian Jew physicist, from whom the Nobel Prize was unjustly withheld. The events, dreams and memories of these two women, pacifists and scientists, during an imaginary but likely to happen night spent at the frontline during the First World War, are presented in parallel with the events and their professional encounters in real life. Paradoxically, the scientific discoveries of Marie Curie and Lise Meitner, two sincere believers in the possibility of human understanding and peace, enabled the construction of the most terrifying weapon world was ever faced with – the atomic bomb.